OP0253 AUTOANTIBODY STATUS IN DERMATOMYOSITIS AND POLYMYOSITIS PATIENTS DEFINES BOTH CANCER RISK AND SURVIVAL WITH ANA NEGATIVITY IN CASES WITH CONCOMITANT CANCER HAVING A WORSE SURVIVAL. (2nd June 2020) - Watad, A.; Mcgonagle, D.; Lidar, M.; Bragazzi, N. L.; Comanesther, D.; Cohen, A.; Amital, H.
Abstract : Background: We previously reported that ANA-negative cases with systemic sclerosis (SSc) and concomitant cancer had a worse survival than ANA-positive cases with associated cancer possibly suggesting that humoral mediated autoimmunity conferred a survival advantage (1). Dermatomyositis (DM) and polymyositis (PM) are two immune-mediated myopathies associated with numerous autoantibodies. Objectives: The present large-scale, population-based study tested the hypothesis that humoral autoimmunity associated with cancer in solid/haematological malignancies impacted on DM/PM patient survival. Methods: Over 2000 cases with either DM or PM were recruited from the Clalit Health Service (CHS) chronic diseases registry, one of the largest healthcare maintenance Israeli organization, serving approximately half of the entire country's population. Over 10000 matched controls were recruited. The data collected range from 2000 to 2018. Results: Altogether 12, 278 subjects were recruited (2, 085 cases, and 10, 193 controls, 5, 042 males, 41.1%, and 7, 236 females, 58.9%). Among cases, 1, 475 individuals (70.7%) were diagnosed with DM, whereas 610 (29.3%) with PM. Mean age was 47.81±22.51 years. 1, 379 cases of cancers (11.2%) were diagnosed. At the univariate analysis and as expected, the rate of malignancies was significantly (p<0.0001) higher in DM/PM (n=361, 17.3%) with respect to controls (n=1, 018, 10.0%). Concerning prognosis, ANA positivity in PM/DM was associated with a better prognosis for all cancers (OR 0.39 [95% 0.24-0.63], p=0.0001). For individual cancer types; thyroid cancer (OR 0.39 [95% 0.24-0.63], p=0.0001), gastric cancer (OR 0.40 [95% 0.25-0.64], p=0.0001), kidney cancer (OR 0.39 [95% 0.24-0. 62], p=0.0001), acute leukaemia (OR 0.40 [95% 0.25-0.65], p=0.0002), non-Hodgkin's lymphoma (OR 0.39 [95% 0.25-0.63], p=0.0001), but not for myelodysplastic syndrome. The main cancers linked to PM/DM were thyroid cancer (OR 3.17 [95%CI 2.27-4.43]), gastric cancer (OR 5.96 [95%CI 4.24-8.38]), kidney cancer (OR 3.83 [95%CI 1.02-14.31], p=0.0462), and myelodysplastic syndrome (OR 2.01 [95%CI 1.17-3.46], p=0.0111). Regarding gastric cancer, positivity for anti-RNP (OR 5.68 [95%CI 3.02 to 10.71], p<0.0001), anti-SSA (OR 21.99 [95%CI 11.21 to 43.14], p<0.0001), and anti-Jo1 (OR 12.23 [95%CI 7.12 to 21.01], p<0.0001) was associated with a higher risk of cancer development. Conclusion: ANA positivity is an independent predictor of favorable prognosis in PM/DM patients with cancer, possibly suggesting that cancer directed humoral autoimmunity may have some benefit. Therefore, humoral autoimmunity in SSc and PM/DM is a broad mechanism that confers a survival advantage and is relevant for disease understanding and elucidating optimal anti tumoural immunity in the current age of cancer immunotherapy. References: [1]Watad A, McGonagle D, Bragazzi NL, Tiosano S, Comaneshter D, Shoenfeld Y, Cohen AD, Amital H. Autoantibody status in systemic sclerosis patients defines both cancer risk and survival with ANA negativity in cases with concomitant cancer having a worse survival. Oncoimmunology. 2019 Mar 24;8(6):e1588084. Disclosure of Interests: Abdulla Watad: None declared, Dennis McGonagle Grant/research support from: Janssen Research & Development, LLC, Merav Lidar: None declared, Nicola Luigi Bragazzi: None declared, Doron Comanesther: None declared, Arnon Cohen: None declared, Howard Amital: None declared